2017
DOI: 10.1007/s00436-017-5519-6
|View full text |Cite
|
Sign up to set email alerts
|

New Entamoeba group in howler monkeys (Alouatta spp.) associated with parasites of reptiles

Abstract: Our knowledge of the parasite species present in wildlife hosts is incomplete. Protozoans such as amoebae of the genus Entamoeba infect a large variety of vertebrate species, including NHPs. However, traditionally, their identification has been accomplished through microscopic evaluation; therefore, amoeba species have not always been identified correctly. We searched for Entamoeba spp. using a fragment of the small subunit rDNA in free-ranging howler monkeys (Alouatta palliata and A. pigra) from southeast Mex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…bovis clade and folivorous primates, but expands known diversity. We also detected two novel Entamoeba phylotypes in Alouatta pigra, including one previously found in A. pigra [77]. Entamoeba phylotype diversity in the platyrrhine monkeys and apes is lower than in cercopithecines.…”
Section: Protistsmentioning
confidence: 48%
“…bovis clade and folivorous primates, but expands known diversity. We also detected two novel Entamoeba phylotypes in Alouatta pigra, including one previously found in A. pigra [77]. Entamoeba phylotype diversity in the platyrrhine monkeys and apes is lower than in cercopithecines.…”
Section: Protistsmentioning
confidence: 48%
“…Villanueva-García et al [39] recently reported SSU-rDNA sequences of an apparently novel Entamoeba in two species of Howler monkey. Because these were only partial sequences they were given a conditional lineage identifier [34] rather than a RL number.…”
Section: " "mentioning
confidence: 99%
“…For example, if Villanueva-García et al [39] had used species-specific primers for Entamoeba, the two novel Entamoeba species found in Howler monkeys (CL8 and RL6) would not have been identified -the samples would have been negative even though Entamoeba organisms were present. Sequencing of products amplified using genus-specific primers may seem the best way forward, but there is a catch.…”
Section: " "mentioning
confidence: 99%
“…Blastocystis , a protozoan that recently gained medical importance (Vargas-Sanchez et al ., 2015), was detected in the two above-mentioned Mexican howler monkeys in southern Mexico (Villanueva-Garcia et al ., 2017 a ). It is also worthy of attention that a new Entamoeba clade has also recently been described in these primate species (Villanueva-Garcia et al ., 2017 b ). Finally, a study in a wild rodent community revealed Eimeria spp.…”
Section: Current Knowledge Of Parasites In Mexican Wildlifementioning
confidence: 99%